Kajian Kualitas Layanan KTP-Elektronik Bagi Penyandang Disabilitas dan Lansia di Kabupaten Mojokerto - Anindya, Naurah Tsani; Fanida, Eva Hany (Publika, 2024)
Vulnerable groups such as people with disabilities and the elderly often find it difficult to access public services, such as e-KTP recording. Therefore, the Mojokerto District Population and Civil Registration Office innovated the Teman Dilan, which is an at-home e-KTP recording service for vulnerable communities. This study aims to analyze Teman Dilan Service Innovation in Mojokerto District based on Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Nomor 91 Tahun 2021. The type of research used is descriptive qualitative. Data were collected through observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusions. The results showed that Teman Dilan Service Innovation has a novelty, which is recording e-KTP at home and has a difference in procedures with general e-KTP recording services, but is still constrained by terrain conditions. On the effective indicator, Teman Dilan innovation can increase e-KTP ownership and the community is satisfied with the service, although there are constraints on the number of officers and community conditions. This innovation is useful in improving the accuracy of population data and access to government programs, but social assistance is still uneven. On the easy to spread indicator, the design of this innovation can be adapted even though it has not been implemented by other institutions and the dissemination of this innovation through social media and village governments. Based on sustainable indicators, The Teman Dilan Service innovation is able to be implemented in the long term supported by the availability of budget and infrastructure. The main suggestion given is that the government needs to carry out regular control and evaluation to improve the performance of Teman Dilan Service Innovation.